31 'I'm fine': exploring patient and carer assertions of status in advanced COPD and clinical implications. Issue 3 (1st September 2017) - Moore, Caroline; Gardener, Anita Carole; Farquhar, Morag; Ewing, Gail; Duschinsky, Robbie
Abstract : Introduction: Patients can be reluctant to say that they need help and support, telling clinicians they are ''fine'' despite having unmet needs. Research with patients in mental health settings suggests that when patients do this they are less likely to follow their treatment plans, and that their informal carers may be at a risk of depression. To date these findings have not been explored in patients with advancing physical health conditions or their carers. Aim: To explore the presence and role of "I'm Fine" or equivalent assertions for patients with advanced COPD and their carers; and to examine the impact denials of support needs may have on their health and service-use. Methods: Criteria based on Attachment Theory was used to identify 'I'm Fine' cases from the Living with Breathlessness Study (LWB) dataset of 235 patient and 115 carer qualitative interview transcripts. Data will be further analysed to explore discourses within cases using a Framework approach. Results: Patients and carers who asserted they were 'fine' and not in need of further clinical support despite unmet needs had a distinct profile. Patients' self-management attitudes and beliefs included minimising the effects and symptoms towards COPD, avoidance of thinking about the future and using stoical language in an attempt to downplay experiences. Carers focused on the needs of the patient whilst downplaying their own problems or distress. Conclusion: Better understanding of the processes and implications of assertions of status will support future work on interventions to support patients and carers.